Penelitian Morfologi Teritisan dengan Sistem Kinetik dan Efektifitasnya pada Bangunan Kantor - Sjarifudin, Firza Utama (Bina Nusantara University, 2011)
Shading device serves as a shade and protection against negative influences caused by the uncertain external conditions. This article discusses the study of kinetic shading system and evaluates its effectiveness against a wide range of environmental factors and their effects on building. The study performs simulation of thermal factors, day lighting, airflow, and energy generation. Morphological types of shading device to be tested are systems of overhang, folded, horizontal louvre, and vertical louvre. The test results demonstrate that kinetic system obtains more advantages and effectiveness than the standard and static systems do. Therefore, it can be concluded that this study is able to be used as a reference for designing kinetic shading device which is responsive to environmental factors.